Tanner's tempo of growth in adolescence: recent SITAR insights with the Harpenden Growth Study and ALSPAC - Cole, T. J. (Annals of human biology, 2020)
Background: James Tanner emphasised the "tempo" of growth, i.e. the adolescent spurt as summarised by its timing (age at peak velocity or APV) and intensity (peak velocity, PV). Aim: The paper applies the SITAR growth curve model to pubertal growth data with the aim of clarifying the growth pattern across multiple measurements and the spectrum of APV and PV. Subjects and methods: Data for 7-20 years on ten anthropometric measurements in 619 children from the Harpenden Growth Study, and on height in 10410 children from the ALSPAC study, were analysed using SITAR (SuperImposition by Translation And Rotation). SITAR models pubertal growth as a mean curve with APV and PV fitted as subject-specific random effects, and a random measurement intercept. Results: Mean APV for Harpenden girls and boys averaged 12.0 and 13.9 years across the ten measurements. PV expressed as percent per year lay in the narrow range 4-8%. Splitting the ALSPAC subjects into 9 by 5 APV and PV groups and fitting separate SITAR models to each group confirmed SITAR's good fit while highlighting the spectrum of growth patterns. Conclusion: SITAR works well to summarise pubertal growth. The disappointment is that Tanner did not live to see it in action.